Checklist of mammals from Gunung Silam, Sabah, Malaysia. - Besar, Ketol; F. A., Anwarali; Wahap, Marni; Isa, Sait; Maklarin, Lakim; Paul Imbun, Yambun; Mohd Azib, Salleh; Mustafa, Abdul Rahman; Mohd Tajuddin, Abdullah (2009)
Field survey was conducted in Mount Silam (Gunung Silam), Lahad Datu, Sabah in September 1995 to inventory the diversity of mammals. A total of 23 species of mammals representing 15 families were recorded. The most captured small mammal species was the Short-nosed Fruit Bat (Cynopterus brachyotis) and the most encountered large mammal was the Bearded Pig (Sus barbatus). This paper presents a preliminary mammalian list for Mount Silam.